Hubungan Penggunaan Diapers dengan Kemampuan Toilet Training pada Anak Usia Toddler di Desa Sausu Torono Kecamatan Sausu Kabupaten Parigi Moutong - Katrina Feby Lestari; Ivon Carolina Samatara; Ni Nyoman Udiani (Universitas Muhammadiyah Manado, 2020)
One of the hard motoric that should be done by toddler is toilet training ability to control their bowel movement and urination. Based on interview report mentioned that children in 3 years old still have difficulties in controlling the bowel movement and urination and instead of it they wear diapers. Diapers wearing in long time and continously become one of barrier for children in performing toilet training. The aims of research to analys the correlation of diapers wearing with toilet training ability toward toddler in Sausu Torono Village. The type of research is quantitaive with analyses design and cross secional approached. Population is parents who have children in toddler age. The total sampling is 50 respondents that determined by slovin formula and taken by purposive sampling technique. Data analysed by chi square test. Diapers wearing as a independent variable and toilet training ability as a dependent variable. The result shown that about 26 children (52%) have diapers wearing routinely and 30 children (60%) have succesful in toilet training. The result of analyses found P value = 0,008 (P<0,05) and could be concluded that have correlation of diapers wearing with toilet training ability toward toddler in Sausu Torono Village, Sausu Subdistrict, Parigi Moutong Regency.